2004
DOI: 10.2139/ssrn.609306
|View full text |Cite
|
Sign up to set email alerts
|

Leadership and Team Cohesiveness Across Cultures

Abstract: This study examines the relation between leadership and team cohesiveness in different societal cultures. We expect direct effects of societal culture on leadership and team cohesiveness, as well as a moderating effect of culture on the relationship between leadership and cohesiveness. Data were collected from 29,868 managers and 138,270 corresponding team members in 80 countries. Multilevel analysis was used to test hypotheses, relating societal individualism-collectivism (IC), with directive and supportive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 80 publications
(81 reference statements)
1
41
0
2
Order By: Relevance
“…Team cohesiveness is well-known as an important element of team dynamics. Defined as "the degree to which members of a group or team are attracted to a group or team and motivated to remain part of it" [48] (p. 359), team cohesiveness has been a focus of organizational academic research to develop efficient human resource strategies that improve value involving employees' membership, cooperative attitudes and teamwork performance [49].…”
Section: Moderating Roles Of Volunteer Team Cohesiveness Upon the Relmentioning
confidence: 99%
“…Team cohesiveness is well-known as an important element of team dynamics. Defined as "the degree to which members of a group or team are attracted to a group or team and motivated to remain part of it" [48] (p. 359), team cohesiveness has been a focus of organizational academic research to develop efficient human resource strategies that improve value involving employees' membership, cooperative attitudes and teamwork performance [49].…”
Section: Moderating Roles Of Volunteer Team Cohesiveness Upon the Relmentioning
confidence: 99%
“…Leaders' crafting of shared identity thus has direct implications for group members because people's capacity to categorize themselves in terms of a group membership is a critical determinant of their motivation (and hence performance; Haslam, Powell, & Turner, 2000;van Knippenberg, 2000; see also Wendt, Euwema, & van Emmerik, 2009). Following on from this, because people's self-categorization in terms of group membership relates to the performance of individual group members and the group as a whole (Ellemers, de Gilder, & Haslam, 2004; see also Zaccaro et al, 2002), we expect that leaders' cultivating of shared identity also feeds into group members' perceptions that they as a group are successful and performing well.…”
Section: Leaders' Management Of a Groupmentioning
confidence: 99%
“…For the present study, consideration and initiating structure were chosen because both styles have been shown to have important main effects on numerous criteria that are considered to be fundamental indicators of effective leadership (Euwema, Wendt, & Van Emmerik, 2007;Judge et al, 2004;Wendt, Euwema, & Van Emmerik, 2009). Further, these types of leadership behaviours are particularly relevant to study gender issues because of the documented stereotypes which people hold concerning these styles (Eagly & Johnson, 1990): men are believed to be more forceful, dominant, and motivated to master their environment and thus more inclined to use the initiating structure leadership behaviour.…”
Section: Leadershipmentioning
confidence: 99%
“…The literature on cross-cultural management shows that societal cultural differences have a pervasive influence on leadership behaviours (Hofstede, 2001;House et al, 2004;Van de Vliert, 2006;Wendt et al, 2009). As such, a considerable number of studies have shown that a societal culture helps to explain leadership behaviours (e.g.…”
Section: Q3mentioning
confidence: 99%
See 1 more Smart Citation